2008
DOI: 10.2186/jjps.52.211
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Necessary Mouthguard Thickness. Part 1: From the Viewpoint of Shock Absorption Ability

Abstract: Within the limitations of this study, from the viewpoint of energy absorption ability, the minimum thickness required for a mouthguard is 4 mm, which is generally too large from the viewpoint of player comfort. This finding indicates the necessity of improving the impact absorption ability of mouthguards by considering new designs and developing new materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
107
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(120 citation statements)
references
References 25 publications
4
107
1
8
Order By: Relevance
“…The greater the labial layer thickness of a sports mouthguard, the greater its energy absorption capacity 16,37 and the smaller the transferred maximum force. As a layer thickness of more than 6 mm allegedly handicaps athletes, 20 only the labial part of the dentition, which is most exposed to impacts, should be protected by a layer thickness exceeding 6 mm. Tulunoglu and Ozbek 37 concluded that a mouthguard's thickness is the crucial factor to prevent injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater the labial layer thickness of a sports mouthguard, the greater its energy absorption capacity 16,37 and the smaller the transferred maximum force. As a layer thickness of more than 6 mm allegedly handicaps athletes, 20 only the labial part of the dentition, which is most exposed to impacts, should be protected by a layer thickness exceeding 6 mm. Tulunoglu and Ozbek 37 concluded that a mouthguard's thickness is the crucial factor to prevent injuries.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Previous studies showed that increasing the mouthguards' thickness improved their shock absorption capacities. 20 Different impact energies occur while practicing different sports 21 (Table 1). 20 Different impact energies occur while practicing different sports 21 (Table 1).…”
mentioning
confidence: 99%
“…Si de nombreux facteurs influencent la capacité d'absorption des chocs d'une PIB (matériau utilisé pour sa fabrication, processus de fabrication, géométrie de la PIB), le plus important est son épaisseur [39,41]. Plusieurs études ont montré que la capacité d'absorption des chocs augmente avec l'épais-seur de la PIB [39,41].…”
Section: Critères Techniques De Fabricationunclassified
“…Plusieurs études ont montré que la capacité d'absorption des chocs augmente avec l'épais-seur de la PIB [39,41]. D'un autre côté, plus l'épaisseur de la PIB est importante, plus elle diminue les performances du sportif et gêne sa respiration et son confort [40].…”
Section: Critères Techniques De Fabricationunclassified
See 1 more Smart Citation